Pembangunan Aplikasi Penjualan Ikan Cupang pada Toko Chufunk Berbasis Website - Predy Daniel Halomoan; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
During this covid pandemic, manual sales are not recommended to reduce direct interaction. So the sale is recommended to be done online. This research aims to help Chufunk Stores in selling online by creating a website-based e-commerce application. The development method used in this research is RUP (Rational Unified Process) with software analysis modeling using UML (Unified Modeling Language). Making this e-commerce application using the PHP programming language and using MySQL as the database. The result of this research is an e-commerce application for selling betta fish based on a website.